Challenges for China in the Establishment of Regional Comprehensive Economic Partnership (RCEP) - Marulitua Gultom, Yosua Saut; Fathun, Laode Muhammad (Department of International Relations Universitas Pertamina, 2024)
This research aims to provide a descriptive explanation of how the formation of economic integration through the RCEP case study is able to form a new order of regionalism in the region. This research also tries to explore the challenges for China as the main economic power in the economic integration. This research utilizes the concepts of third wave regionalism and free trade zones through a descriptive qualitative study approach. The research finds that although China and ASEAN are positively on the same track regarding the establishment of RCEP, it is challenged by broader regionalism such as the Sino-Indian rivalry and other similar regionalism mechanism challenges. The article concludes that it is necessary for China to face the challenges by establishing a fair and acceptable cooperation arrangement for the global south so that RCEP can be beneficial for both parties.